2009
DOI: 10.1007/s00467-008-0961-4
|View full text |Cite
|
Sign up to set email alerts
|

Oxidant/antioxidant status and hyperfiltration in young patients with type 1 diabetes mellitus

Abstract: Diabetic nephropathy (DN), a major cause of morbidity and mortality in diabetes, will develop within a subset of type 1 diabetes mellitus (T1DM) patients, and oxidative stress has been implicated in its pathogenesis. To investigate the relationship between indicators of early DN stages (hyperfiltration estimated by creatinine clearance > or =150 ml/min per 1.73 m(2), microalbuminuria) and oxidative stress, a prospective study was conducted in 29 T1DM patients (age 13.89 +/- 4.61 years) and 18 control subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 31 publications
1
30
0
Order By: Relevance
“…The identification of oxidation proteins was made by assay of carbonyl proteins, whose concentration increased in plasma of diabetic children when compared with control; these results are in agreement with previous studies (Dominguez et al, 1998;Hernández-Marco et al, 2009). Carbonyl group formation is considered an early and stable marker for protein oxidation.…”
Section: Discussionsupporting
confidence: 86%
“…The identification of oxidation proteins was made by assay of carbonyl proteins, whose concentration increased in plasma of diabetic children when compared with control; these results are in agreement with previous studies (Dominguez et al, 1998;Hernández-Marco et al, 2009). Carbonyl group formation is considered an early and stable marker for protein oxidation.…”
Section: Discussionsupporting
confidence: 86%
“…In addition to physiological ageing, intrarenal arterial sclerosis is accelerated by longterm hypertension and diabetes mellitus [18]. Diabetes mellitus is complicated with early renal function decline [24,25]. As a result of all these, the course of other primary renal diseases (glomerulonephritis, acute renal failure and endotoxin-induced thrombosis) become accelerated [28,29].…”
Section: Thoracic Oncology C Máthé Et Almentioning
confidence: 99%
“…Chronic systemic hypertension [23] and diabetes mellitus [24,25] accelerate ageing of the kidney. OHTA et al [26] demonstrated higher pulse-wave velocity, a sign of atherosclerosis, in main renal arteries and the renal interlobar arteries of middle-aged patients suffering from hypertension and diabetes mellitus.…”
Section: Thoracic Oncology C Máthé Et Almentioning
confidence: 99%
“…Activation of multiple metabolic pathways in diabetes leads to increased generation of reactive oxygen species. However, oxidative effects of reactive oxygen species are generally controlled by both endogenous and exogenous antioxidants [23].…”
Section: Discussionmentioning
confidence: 99%